Interactive effects of nutrients and salinity on zooplankton in subtropical plateau lakes with contrasting water depth - Yang, Li-Juan; Tao, Ya; Jiang, Xia; Wang, Ying; Li, Ye-Hao; Zhou, Long; Wang, Pu-Ze; Li, Yuan-Yuan; Zhao, Xu; Wang, Hai-Jun; Jeppesen, Erik; Xie, Ping (Frontiers in Environmental Science, 2023)
Both eutrophication and salinization are growing global environmental problems in freshwater ecosystems, threatening the water quality and various aquatic organisms. However, little is known about their interactive effects on lakes of different depths. In this research, zooplankton assemblages were compared over four seasons in eight Yunnan Plateau lakes with different eutrophic states, salinization levels, and water depths. The results showed that: 1) the species number (SN), density (DZoop), and biomass (BZoop) of zooplankton exhibited strong seasonal dynamics, being overall higher in the warm seasons. 2) Four-season mean and summer data revealed highly significant positive relationships of SN, DZoop, and BZoop with total nitrogen (TN), total phosphorus (TP), and phytoplankton chlorophyll a (Chl a). 3) SN, DZoop, and BZoop displayed a unimodal relationship with salinity, peaking at 400-1000 μS/cm (conductivity, Cond). 4) The two large-sized taxa (cladocerans and copepods) decreased with eutrophication and conductivity, while increasing trends were found for the two small-sized taxa (rotifers and protozoans). The average body mass (biomass/density) of crustaceans decreased with increasing TN, TP, Chl a, and Cond. Our findings indicate that zooplankton may be more vulnerable in deep lakes than in shallow lakes when exposed to salinity stress even under mesotrophic conditions, and the overall decrease in size in zooplankton assemblages under the combined stress of eutrophication and salinization may result in a lowered grazing effect on phytoplankton.